2016
DOI: 10.1007/s13205-016-0370-5
|View full text |Cite
|
Sign up to set email alerts
|

Feather degradation potential of Stenotrophomonas maltophilia KB13 and feather protein hydrolysate (FPH) mediated reduction of hexavalent chromium

Abstract: An efficient keratinolytic strain of Stenorophomonas maltophilia KB13 was isolated from feather disposal site of Bilaspur, Chhattisgarh, India. The strain could metabolize 10 g/l chicken feathers as sole source of carbon and nitrogen. Soluble protein, amino acid, and cysteine content were found to be maximum (690.6 ± 8.7, 688.9 ± 9.12 and 21 ± 0.36 µg/ml, respectively) at late logarithmic phase of growth. Protease and keratinase activity reached its maximum level (103.26 ± 7.09 and 178.5 ± 9.10 U/ml) at the 4t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…Cr(VI) reduction was significantly inhibited by mercury ions (Hg(II)) indicating the role of sulfur-containing amino acids in reduction process. FTIR analysis confirmed that chromium reduction occurred due to oxidation of amino acids such as cysteine and cystine[93].Gram-negative bacteria Acinetobacter belongs to the wider class of Gamma-proteobacteria and has been employed for Cr(VI) reduction. It is a bacterium tolerant to many metals and oxygen demanding pollutants.…”
mentioning
confidence: 94%
“…Cr(VI) reduction was significantly inhibited by mercury ions (Hg(II)) indicating the role of sulfur-containing amino acids in reduction process. FTIR analysis confirmed that chromium reduction occurred due to oxidation of amino acids such as cysteine and cystine[93].Gram-negative bacteria Acinetobacter belongs to the wider class of Gamma-proteobacteria and has been employed for Cr(VI) reduction. It is a bacterium tolerant to many metals and oxygen demanding pollutants.…”
mentioning
confidence: 94%
“…3.4.21/24/99.11), can degrade keratin proteins and apply in poultry wastes' bioremediation by degrading and recycling keratinous wastes into useful byproducts. e protease enzyme, keratinase produced from Stenotrophomonas maltophilia KB13, has shown significant activity on the biodegradation of chicken feathers [126]. e keratinase enzyme produced by Bacillus sp.…”
Section: Dehydrogenasementioning
confidence: 99%
“…have shown significant hydrolysis of keratinous wastes from poultry [129]. e products released from the degradation of feathers are rich in amino acids and nutrients and thus can be used as feed additives, fertilizers for plant growth [130], free radical scavengers, ferric ion reducing agent [131], and toxic hexavalent chromium reducing agent [126]. Keratinase is used in enzymatic environment-friendly dehairing processes in the leather industry to replace the traditional chemicals CaO and Na 2 S, which prevent toxic waste release in water bodies to avoid pollution [132].…”
Section: Dehydrogenasementioning
confidence: 99%
“…strain kr2 8 , Aeromonas hydrophila strain FB3 8 , Stenotrophomonas spp. [9][10][11] , Chryseobacterium spp [12][13] . A fungal isolate from crocodilian feces was reported to degrade chicken feather waste within 10 days 14 .…”
Section: Introductionmentioning
confidence: 99%